Resolving shortages of prescription drugs: the case for public-private collaboration - Eric Efraim Katz (BMC, 2017)
Abstract The recent IJHPR article by Schwartzberg and colleagues presents new data on the growing problem of prescription drug shortages. Resolving shortages typically involves many participants: government, industry, physicians and healthcare facilities. Israel has a strong record of informal collaboration that can fix drug shortages quickly. The success of Israel's informal collaborations, as well as its formal partnerships, deserves broader recognition at home and more attention from the international community.